The Effect of Direct Renin Inhibition Alone and in Combination With ACE Inhibition on Endothelial Function, Arterial Stiffness, and Renal Function in Type 1 Diabetes - Cherney, David Z.I. (American Diabetes Association, 2012)
OBJECTIVE: Diabetes is associated with renin-angiotensin system (RAS) activation, leading to renal and systemic vascular dysfunction that contribute to end-organ injury and significant morbidity. RAS blockade with ACE inhibitors reduces, but does not abolish, RAS effects. Accordingly, our aim was to determine if direct renin inhibition alone, and in combination with an ACE inhibitor, corrects early hemodynamic abnormalities associated with type 1 diabetes. RESEARCH DESIGN AND METHODS: Arterial stiffness (augmentation index), flow-mediated vasodilatation (FMD), and renal hemodynamic function (inulin and paraaminohippurate clearance) were measured at baseline under clamped euglycemic and hyperglycemic conditions (n = 21). Measures were repeated after 4 weeks of aliskiren therapy and again after aliskiren plus ramipril. RESULTS: Blood pressure–lowering effects of aliskiren were similar during clamped euglycemia and hyperglycemia. Combination therapy augmented this effect under both glycemic conditions (P = 0.0005). Aliskiren reduced arterial stiffness under clamped euglycemic and hyperglycemic conditions, and the effects were augmented by dual RAS blockade (−3.4 ± 11.2 to −8.0 ± 11.5 to −14.3 ± 8.4%, respectively, during euglycemia, P = 0.0001). During clamped euglycemia, aliskiren increased FMD; dual therapy exaggerated this effect (5.1 ± 3.3 to 7.5 ± 3.0 to 10.8 ± 3.5%, repeated-measures ANOVA, P = 0.0001). Aliskiren monotherapy caused renal vasodilatation during clamped hyperglycemia only. In contrast, dual therapy augmented renal vasodilatory effects during clamped euglycemia and hyperglycemia. CONCLUSIONS: In patients with uncomplicated type 1 diabetes, aliskiren-based dual RAS blockade is associated with greater arterial compliance, FMD, and renal vasodilatation.